Celebrating the victory and purification: halal-bihalal tradition in the Mangkunegaran Palace 1945-1978 - Nulhasanah, Lisan; Hakiman (SHAHIH: Journal of Islamicate Multidisciplinary, 2023)
This study aims to analyze the history of halal-bihalal gathering held in the Mangkunegaran Palace. The tradition was carried out distinctively during the Mangkunegara VIII era in 1945-1978. The period marked the shift from the Colonial era to the Independent era of Indonesia, resulting in the dynamics of procession and aim of halal-bihalal. The culture-historical approach was employed to determine the specific pattern of phenomenon and to understand the morphology of culture. The stages of historical method, namely heuristics, criticism, historiography, and interpretation, were done. The results of research based on the theory of symbolism and the role of power show that halal-bihalal gathering in the Mangkunegaran reflected the social classes in which the invited guests with upper social level occupied the very very important personal seats. Nevertheless, the event also brought positive impact since people from various backgrounds could gather peacefully and eliminate the conflicts among the classes. As an implication, the tradition was perceived as an important event and held regularly. It was also popular outside the palace and imitated by Islamic organizations using the same term, halal-bihalal.